Integrative Proteo-Genomic Analysis for Recurrent Survival Prognosis in Colon Adenocarcinoma - Ai, FeiYan; Wang, Wenhao; Liu, Shaojun; Zhang, Decai; Yang, Zhenyu; Liu, Fen (Frontiers in Oncology, 2022)
Background: The survival prognosis is the hallmark of cancer progression. Here, we aimed to develop a recurrence-related gene signature to predict the prognosis of colon adenocarcinoma (COAD). Methods: The proteomic data from Clinical Proteomic Tumor Analysis Consortium (CPTAC) and genomic data from the cancer genomic maps (TCGA) dataset were analyzed to identify co-differentially expressed genes (cDEGs) between recurrence samples and non-recurrence samples in COAD using Limma package. Functional enrichment analysis, including GO and KEGG pathway was conducted. Univariate and multivariate cox regression were applied to identify independent prognostic feature cDEGs and established the signature whose performance was evaluated by Kaplan-Meier curve, receiver operating characteristic (ROC), Harrell's concordance index (C-index) and calibration curve. The area under the receiver operating characteristic (ROC) curve (AUROC) and a nomogram were calculated to assess the predictive accuracy. GSE17538 and GSE39582 were used for external validation. Quantitative real time PCR was carried out to validate our findings. Results: We identified 86 cDEGs in recurrence samples compared with non-recurrence samples. These genes were primarily enriched in the regulation of carbon metabolic process, fructose and mannose metabolism and extracellular exosome. Then, an eight-gene based signature (CA12, HBB, NCF1, KBTBD11, MMAA, DMBT1, AHNAK2 and FBLN2) was developed to separate patients into high-risk and low-risk groups. Patients in the low-risk group had significantly better prognosis than those in the high-risk group. Four prognostic clinical features, including pathologic M, N, T and RS model status were screened for building the nomogram survival model. The PCR results suggested that CA12 and AHNAK2 were significantly upregulated, while MMAA and DMBT1 were downregulated in tumor sample compared with adjacent tissues, as well as in non-recurrent samples compared non-recurrent samples in COAD. Conclusion: These identified recurrence-related gene signature might provide an effective prognostic predictor and promising therapeutic targets for COAD patients.